The Constitutionality of Inheritance Rights for Extramarital Children: Assessing the Legal Response under Balinese Customary Law - Sujana, I Nyoman; Maruf, Irma Rachmawati (Faculty of Law, Hasanuddin University, 2024)
This article analyzes the inheritance rights of extramarital children under the post-Constitutional Court decision of Balinese customary law. Any child born of unmarried parents or out of adultery is stigmatized as an extramarital child (walad al zina) for his entire life and forbidden from inheriting an estate from his biological father. This legal issue is chosen as the main subject of this study is because of the legal circumstance in which the Balinese community does not grant status to extramarital children in matters of inheritance from the Purusa line. Hindu-Balinese religious leaders such as Parisada and the Traditional Village Council have never upheld the Constitutional Court’s ruling that states that children born out of wedlock have civil relations with their biological fathers. Islamic religious leaders have followed up on the Constitutional Court’s decision by issuing a fatwa of the Indonesian Ulema Council (MUI). The fatwa imposes an obligation on biological fathers to separate their wealth for a guarantee of life to children. Applying the statutory approach, conceptual approach, sociological approach, and case approach, it can be understood that children born out of wedlock (the Balinese call it begin at children) have no status as heirs in the Purusa line but have inheritance rights from their mother and their mother’s family.